CYTOTOXICITY OF METHANOLIC EXTRACT OF PISONIA ACULEATA L. LEAF - SHWETA P. GHODE (SHWETA A. CHINTALWAR); B. RAJKAPOOR; PRASHANT D. GHODE (International Journal of Pharma and Bio Sciences, 2012)
Cytotoxicity of Methanolic extracts of Pisonia aculeata (MPA) was evaluated using three human cancer cell lines [Human Laryngeal Epithelial Carcinoma cell (Hep2), Human Colon Cancer cell (HT-29) and Human Breast cancer cells (HBL-100)]. The in vitro cytotoxicity was done by Tryphan blue dye exclusion method, MTT assay and Apoptosis. Cells were treated for 72 hrs with various concentration of MPA (31.25-500 mg/ml), the relative cell survival progressively decreased in a dose dependant manner. The IC50 of the MPA was found to be 280, 200 & 340 mg/ml by Tryphan blue dye exclusion method & 130,100 &170 mg/ml by MTT assay. Among the tested cell lines, MPA was more selective cytotoxic against HT-29 cell line than Hep2 & HBL-100 cells. Extensive apoptotic alterations were observed in MPA (500 µg/ml) by Hoechst staining & more than 30% of cells underwent apoptosis upon a single dose (500 µg/ml) of the MPA after 48 hrs.